Crossover to Bilateral Repetitive Transcranial Magnetic Stimulation: A Potential Strategy When Patients Are Not Responding to Unilateral Left-Sided High-Frequency Repetitive Transcranial Magnetic Stimulation. Issue 1 (March 2019) - Cristancho, Pilar; Trapp, Nicholas T.; Siddiqi, Shan H.; Dixon, David; Miller, J. Philip; Lenze, Eric J.
Abstract : Abstract: Clinical trials using left-sided repetitive transcranial magnetic stimulation (rTMS) report remission rates of 14% to 32.6%. A large percentage of patients would not achieve remission with standard rTMS treatment. The question of what clinicians should do when a patient is not responding to standard high-frequency (HF) left-sided rTMS remains unanswered. This prospective case series examines whether crossover to bilateral stimulation enhances antidepressant outcomes in patients not responding to unilateral rTMS. Patients in a major depressive episode received an rTMS clinical protocol of 4 to 6 weeks' duration. Stimulation began with HF rTMS (10 Hz) over the left dorsolateral prefrontal cortex (range, 3000–5000 pulses per session). A total of 17 patients without sufficient clinical improvement early in their rTMS course received 1-Hz rTMS (range, 600–1200 pps) over the right dorsolateral prefrontal cortex (added to the HF left-sided stimulation). Hamilton Depression Rating Scale scores decreased from 13.9 ± 3.9 (mean ± SD) from the start of augmentation to 12.2 ± 5.8 at the end of acute treatment, a 1.7-point change, Cohen d effect size = −0.35, 95% confidence interval, −1.01 to − 0.34, suggesting improvement. Remission rate in this sample was 24% (4/17). This case series indicates that crossover to bilateral stimulation is a feasible and potentially effective strategy when patients are not improving with standard rTMS. A randomized controlled trial comparing crossover versus standard rTMS is needed to determine the efficacy of this paradigm.